1989
DOI: 10.1080/00140138908966852
|View full text |Cite
|
Sign up to set email alerts
|

Local muscular strain dependent on the direction of horizontal arm movements

Abstract: Manual material handling still plays an important role in assembly work as well as in the service industry. By means of an ergonomic layout of working places, the effects of disadvantageous working conditions, especially static load resulting from unfavourable postures of the body as well as unnecessary physiological cost arising from body movements may be avoided. In this context knowledge about the optimum directions of horizontal arm movements is fundamental. Therefore by means of advanced methods of multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Literature regarding the eVect of cooling on EMG activity is contradictory, but several authors have found that EMG activity is increased in cold conditions (Petrofsky and Lind 1980;Winkel and Jørgensen 1991;Hammarskjöld et al 1992;Meigal et al 1998;Oksa et al 2002;). It has also been shown that muscular strain depends on the direction of movement (Strasser and Keller 1989), and movement in a 30° direction in the horizontal plane causes less than half of the muscular load compared to directions between 90° and 160° (Strasser and Muller 1999). The results of this study support this Wnding, since the increase of a-EMG was signiWcantly higher particularly at extreme angles of the trajectories (200° and 220°).…”
Section: Discussionsupporting
confidence: 87%
“…Literature regarding the eVect of cooling on EMG activity is contradictory, but several authors have found that EMG activity is increased in cold conditions (Petrofsky and Lind 1980;Winkel and Jørgensen 1991;Hammarskjöld et al 1992;Meigal et al 1998;Oksa et al 2002;). It has also been shown that muscular strain depends on the direction of movement (Strasser and Keller 1989), and movement in a 30° direction in the horizontal plane causes less than half of the muscular load compared to directions between 90° and 160° (Strasser and Muller 1999). The results of this study support this Wnding, since the increase of a-EMG was signiWcantly higher particularly at extreme angles of the trajectories (200° and 220°).…”
Section: Discussionsupporting
confidence: 87%
“…Low back disorders have been associated with working in a forward, bent position (Vinga˚rd et al, 2000). In other studies the relationships between poorly designed workplaces resulting in poor posture and disorders of the musculoskeletal system have been described (Kilbom, 1988;Louhevaara et al, 1990;Ohlsson et al, 1989;Strasser et al, 1989).…”
Section: Article In Pressmentioning
confidence: 98%
“…5,6,28 The APDF model, which was described and illustrated by Jonsson,29 states that the static level of muscle activity is the percentage of MVC that is below the lowest 10% of the cumulative RMS EMG signal, whereas the dynamic level (90th percentile APDF) is the percentage of MVC that is above the greatest 10% of the cumulative EMG signal.…”
Section: Wrist Positionmentioning
confidence: 99%